2016
DOI: 10.5511/plantbiotechnology.16.0217c
|View full text |Cite
|
Sign up to set email alerts
|

A fluorometric assay for quantification of fucoidan, a sulfated polysaccharide from brown algae

Abstract: Brown algae contain a fucose-rich sulfated polysaccharide called fucoidan which is a constituent of the extracellular matrix. In recent years, fucoidan has attracted much attention for its pharmaceutically important biological activities. To develop a superior method for fucoidan quantification, we investigated several cationic dyes with potential interaction with the negatively charged sulfate groups of fucoidan and found that a commercially available fluorescent dye, SYBR Gold nucleic acid gel stain, showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Fucoidan Puri cation Method 2 -In the second method, puri cation of freeze-dried fucoidan fractions from Cystoseira sp. and Padina pavonica were carried out according to Yamazaki et al (2016) with some modi cations. Dried fucoidan pellets of Cystoseira sp.…”
Section: Fucoidan Extraction and Puri Cationmentioning
confidence: 99%
“…Fucoidan Puri cation Method 2 -In the second method, puri cation of freeze-dried fucoidan fractions from Cystoseira sp. and Padina pavonica were carried out according to Yamazaki et al (2016) with some modi cations. Dried fucoidan pellets of Cystoseira sp.…”
Section: Fucoidan Extraction and Puri Cationmentioning
confidence: 99%
“…Therefore, an analytical method for fucoidan analysis must be developed. Several analytical methods for fucoidan analysis have been developed, including fluorometric assays and UV spectrophotometry (Venkatesan et al, 2018;Yamazaki et al, 2016). However, because herbal extracts are composed of several substances, they are not likely to be simple to apply, and the process requires the isolation of fucoidan from the other components.…”
Section: Figure 1 Chemical Structure Of Fucoidanmentioning
confidence: 99%
“…Consequently, it is also challenging to determine the fucoidan release from a hydrogel over time. To prove the incorporation of fucoidan into the hydrogel, a protocol published by Yamazaki and colleagues [34] was adapted. Yamazaki and colleagues demonstrated that the nucleic acid stain SYBR Gold can be used to quantify the concentration of fucoidan solutions.…”
Section: Preparation and Physicochemical Characterization Of The Fuco...mentioning
confidence: 99%
“…Figure 5. Fucoidan detection inside the hydrogel and fucoidan release tocol from Yamazaki and colleagues [34] was adapted to detect fucoid SYBR Gold nucleic acid stain allowed detecting different fucoidan amo Hydrogels with and without fucoidan were incubated in PBS for 6 days the hydrogel was detected on day 0, 2, and 6 using SYBR Gold. Expe times (n = 3).…”
Section: Preparation and Physicochemical Characterization Of The Fuco...mentioning
confidence: 99%
See 1 more Smart Citation